Prostate specific antigen bounce after intensity-modulated radiation therapy in an Asian population - Yu Guang Tan; Weber Lau Kam On; Hong Hong Huang; Terence Tan Wee Kiat (Asian Journal of Urology)
Objective: Serum prostate specific antigen (PSA) is commonly used to evaluate treatment response after definitive radiation therapy (RT). However, PSA levels can temporarily rise without a clear reason, termed “PSA bounce”, and often engender great anxiety for both patients and physicians. The present study aimed to determine the prevalence and factors that predict “PSA bounce” after intensity-modulated radiation therapy (IMRT), and the relevance to biochemical failure and cancer recurrence in an Asian population. Methods: We retrospectively reviewed 206 patients who received IMRT for prostate cancer from 2004 to 2012 in the National Cancer Centre Singapore. These patients were followed up with regular PSA monitoring. We defined “PSA bounce” as a rise of 0.1 ng/mL, followed by two consecutive falls. Patients with biochemical failure (PSA nadir + 2 ng/mL) were further evaluated for cancer recurrence. Results: Sixty-one patients (29.6%) experienced “PSA bounce”, at a median time of 16 months and lasted for 12 months. Age remained the most consistent predictor of the incidence, duration and extent of “PSA bounce”. Other contributory factors included baseline PSA, Gleason score and PSA nadir. Hormonal therapy and prostate volume did not affect this phenomenon. Sixteen patients (7.8%) developed biochemical recurrence, at median time of 32 months, of which 11 were confirmed to have metastatic disease. The median follow-up time was 71 months. Conclusion: A younger age predicts PSA bounce incidence, duration and magnitude. The extent of bounce appears to be lower in Asian population. The interval to occurrence and extent of PSA elevation separates PSA bounce from disease recurrence. Keywords: Prostate specific antigen, Prostate specific antigen bounce, Prostate cancer, Intensity modulated radiation therapy